Clinical and biochemical characteristics of type 2 diabetes mellitus (DMt2) at Instituto Nacional de Salud del Niño - Calagua-Quispe, Martha (2012)
Abstract Objective: To determine clinical and biochemical characteristics in type 2 diabetes mellitus (T2DM) in pediatric patients at time of diagnosis. Design: Clinical retrospective study. Setting: Endocrinology Service, Instituto Nacional de Salud del Niño, Lima, Peru. Patients: Children with diabetes mellitus type 2. Methods: Medical records of 187 registered patients with diabetes mellitus were reviewed and 17 (9%) with T2DM were identified. Personal and familiar characteristics, symptoms and biochemical data were obtained. Main outcome measures: Clinical and biochemical characteristics of pediatric patients. Results: Average age at diagnosis was 12.8±3 years, 11 were male (64.7%) and 6 female (35.3%). All were born at term and 17.6% were macrosomic. Fourteen patients (82.4%) had a family history of T2DM. Most frequent symptoms were polyuria, polydipsia, polyphagia and weight loss; 35.3% were overweight, 41.2% obese and 65% showed acanthosis nigricans. Five patients developed ketoacidosis. Some component of the lipid profile was abnormal in 60% with elevation of low-density lipoprotein cholesterol in 46.5%. Anti-insulin antibodies, anti-GAD and islet cell antibodies (anti-ICA) were negative in 85.7% and any of them positive in 14.3%. Conclusions: In this series of children with type 2 diabetes most had a family history of type 2 diabetes, 75% showed classical signs and symptoms of the disorder accompanied by overweight or obesity and dyslipidemia.